Involuntary psychiatric admission in Cyprus: A descriptive correlational study - Kaikoushi, Katerina; Nystazaki, Maria; Chatzittofis, Andeas; Middleton, Nicos; Karanikola, Maria (My University, 2022)
Introduction: Studies on the clinical and socio-demographic characteristics of those involuntarily admitted to psychiatric settings could help professionals and researchers to develop effective, targeted interventions, alternative to compulsory psychiatric care. Aim: The association between socio-demographic and clinical characteristics in adults under involuntary hospitalization for psychiatric treatment in the Republic of Cyprus was assessed. Method: This was a descriptive, cross-sectional and correlational study. Data collection was achieved (December 2016 to February 2018) via a census sampling method. Socio-demographic and clinical data of individuals involuntarily admitted to the reference psychiatric hospital of Cyprus with psychotic symptomatology were recorded. Results: The sample encompassed 144 females and 262 males. The most frequent diagnosis was schizophrenia or a relevant psychotic disorder (72.9%). The most frequent cause of admission was “Disorganized behaviour" along with non-adherence to pharmacotherapy (53.7%). Approximately 42.8% of the participants confirmed positive substance use history, which was more frequently reported in males than in females (88.5% vs. 11.5%, respectively, p < 0.001). Additionally, males were more frequently admitted due to Disorganized behaviour with substance use compared to females (31.3% vs. 4.9%, respectively, p < 0.001), while females were more frequently admitted due to d"Disorganized behaviour with non-adherence to pharmacotherapy (70.1% vs. 44.7%, respectively, p < 0.001). Also, males were more frequently involuntarily hospitalized due to suicidal/selfharming behaviour compared to females (12.2% vs. 5.6%, respectively, p = 0.031). Conclusion: Gender differences were noted in relation to clinical characteristics of the participants, highlighting the need for gender-specific interventions to decrease compulsory psychiatric care, including enhancement of adherence to therapy.
Keywords: Clinical characteristics; Involuntary hospitalization; Psychotic disorder; Socio-demographic characteristics